2009
DOI: 10.1155/2009/756395
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Malignant Peripheral Nerve Sheath Tumours: A Comparison between Sporadic and Neurofibromatosis Type 1-Associated Tumours

Abstract: We studied 123 patients with malignant peripheral nerve sheath tumours (MPNSTs) between 1979 and 2002. However, 90 occurred sporadically whereas 33 were associated with neurofibromatosis type 1 (NF1). Survival was calculated using Kaplan-Meier survival curves and we used Cox's proportional hazards model to identify independent prognostic factors. A 5-year survival for 110 nonmetastatic patients was 54%; (33% NF1 and 63% sporadic P = .015). Tumour stage and site were significant prognostic indicators after univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
3
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 23 publications
(31 reference statements)
4
122
3
6
Order By: Relevance
“…Current treatment options are restricted to complete surgical resection with clear margins; however, the local recurrence of MPNSTs is high (from 32% to 65%; ref. 9).…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment options are restricted to complete surgical resection with clear margins; however, the local recurrence of MPNSTs is high (from 32% to 65%; ref. 9).…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports regarding the utility and limits of FDG-PET for neurogenic tumors. It is known that benign neurogenic tumors often show high FDG accumulation based on the cell density (10,16,17,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…There have been few large studies about survival and those reporting 5-year survival lack consistency, with survival rates in the range of 39% -85%. Few studies have suggested NFI as an independent indicator of poor prognosis in MPNSTs [19]. A combination of clinical, pathological, and immunohistochemistry helps in diagnosing of these tumors.…”
Section: H M Hendam Et Al Open Journal Of Modern Neurosurgerymentioning
confidence: 99%